2010
DOI: 10.1111/j.1600-0722.2010.00729.x
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR and MSX1 contribute to the risk of nonsyndromic cleft lip/palate

Abstract: Recent studies suggest that multiple interacting loci, with possible additional environmental factors, influence the risk for nonsyndromic oral clefts, one of the most common birth defects in humans. Advances in high-throughput genotyping technology allow the testing of multiple markers, simultaneously, in many candidate genes. We tested for associations between 176 haplotype-tagging single nucleotide polymorphisms (SNPs) in 18 candidate genes/loci and nonsyndromic clefts in a case-control study in an Estonian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 42 publications
5
32
0
5
Order By: Relevance
“…In this study 40% of the cases having non syndromal cleft lip/palate did not show any of these gene variants .This may suggest the possibility of involvement of other genes as non syndromal cleft lip/palate is of polygentic nature and studies suggest that other genes like TGFB3, RARA, BCLX3, TGFαA, MTHR, PVLRI [1,14] are involved in the etiology of non syndromal cleft lip/palate.…”
Section: Discussionmentioning
confidence: 63%
“…In this study 40% of the cases having non syndromal cleft lip/palate did not show any of these gene variants .This may suggest the possibility of involvement of other genes as non syndromal cleft lip/palate is of polygentic nature and studies suggest that other genes like TGFB3, RARA, BCLX3, TGFαA, MTHR, PVLRI [1,14] are involved in the etiology of non syndromal cleft lip/palate.…”
Section: Discussionmentioning
confidence: 63%
“…According to the previous studies, mutations in MSX1 can contribute to NSCL/P as many as 2% of the total cases [10,11]. Some studies reported the mutations and/or polymorphisms do not contribute to the anomaly in the examined populations [12,13], and some others reported the variations contribute to the anomaly [14,15]. The unrepeated results from different populations with different ethnicity showed the variability nature of MSX1 for the onset of NS-CL/P.…”
Section: Discussionmentioning
confidence: 95%
“…The chief function of EDN 1 is considered to be the maintenance of the vascular tone. There are few studies that have showed the mutant EDN 1 genes can result in isolated CP [31].…”
Section: Endothelin 1 -Edn1; 6p241mentioning
confidence: 99%